Challenges in Mechanics of Time Dependent Materials, Mechanics of Biological Systems and Materials & Micro-and Nanomechanics, Volume 2 Proceedings of the 2021 Annual Conference & Exposition on Experimental and Applied Mechanics - Amirkhizi, Alireza; Notbohm, Jacob; Karanjgaokar, Nikhil; DelRio, Frank W.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
Challenges in Mechanics of Time-Dependent Materials, Mechanics of Biological Systems and Materials, and Micro-and Nanomechanics, Volume 2 of the Proceedings of the 2021 SEM Annual Conference & Exposition on Experimental and Applied Mechanics, the second volume of four from the Conference, brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Experimental Mechanics, including papers in the following general technical research areas: Characterization Across Length Scales Extreme Conditions & Environmental Effects Damage, Fatigue and Fracture Structure, Function and Performance Rate Effects in Elastomers Viscoelasticity & Viscoplasticity Research in Progress Extreme Nanomechanics In-Situ Nanomechanics Expanding Boundaries in Metrology Micro and Nanoscale Deformation MEMS for Actuation, Sensing and Characterization 1D & 2D Materials Cardiac Mechanics Cell Mechanics Biofilms and Microbe Mechanics Traumatic Brain Injury Orthopedic Biomechanics Ligaments and Soft Materials.
Chapter 1. Advance of Collaborative Twinning Fields in Magnesium AZ31 via the Strain and Residual Intensity Channels in Microscopic Image Correlation -- Chapter 2. Time Dependent Materials Response of Transverse Impact on Model Beams -- Chapter 3. Wearable Device for Tremor Suppression -- Chapter 4. Fractional Viscoelastic Modeling Enabling Accurate Atomic Force Microscope Contact Resonance Spectroscopy Characterization -- Chapter 5. A Method for Measuring Displacement and Strain Around a Crack of Rubber Sheets Using Digital Image Correlation -- Chapter 6. Understanding the Nano-scale Deformation Mechanisms of Polyurea from in-situ AFM Tensile Experiments -- Chapter 7. Porosity Determination and Classification of Laser Powder Bed Fusion AlSi10Mg Dogbones Using Machine Learning -- Chapter 8. Constitutive Modelling of the Dynamic Behavior of Cork Material -- Chapter 9. The Penetration Dynamics of a Violent Cavitation Bubble through a Hydrogel-water Interface -- Chapter 10. Effects of Hydration on the Mechanical Response of a PVA Hydrogel -- Chapter 11. Gaussian Process to Identify Hydrogel Constitutive Model -- Chapter 12. Effect of Host Surface Factors on Biocompatible Adhesion Index -- Chapter 13. Mass Mitigation in Structural Designs Via Dynamic Properties -- Chapter 14. High Temperature Burst Creep Properties of Nuclear-grade FeCrAl Fuel Cladding.
Keywords: Materials; Biomedical engineering; Materials -- Analysis; Nanotechnology; Biomaterials; Mechanics, Applied; Materials Engineering; Biomedical Engineering and Bioengineering; Materials Characterization Technique; Nanoengineering; Biomaterials; Engineering Mechanics; Biomechanics -- Congresses; Materials -- Mechanical properties -- Congresses; Mechanics, Applied -- Congresses